'I am just saying maybe …': Engagement in dissertation defenses. (6th October 2020) - Lau, Ken; Lin, Chia-Yen; Odle, Eric
Abstract: The orientation toward a knowledge-based economy has led to the increasing need to pursue advanced degrees to further improve one's competitiveness in society. Research on postgraduate programs has thus sparked interest from multiple perspectives, among which, generated written artifacts such as dissertations have become the center of attention. However, dissertation defenses (DDs), i.e., the oral output, seem to have not been given due attention from applied linguists, a research gap this paper intends to address. Based on a corpus of five Masters-level DDs collected in an English as a lingua franca context, this study explores the interactions between the DD participants, namely, the students, advisors, and examiners, through the investigation of their use of Engagement resources under the Appraisal theory. It was found that DDs are embedded with face-threatening acts, in which the participants employ a combination of Engagement resources to strategically reify their identities/roles and establish rapport with others.